Geração Blow-up de fotógrafos no Brasil dos anos 60/70 - Silva, Diego Cesar Da [UNIFESP] (2020)
This is a study of the Blow-up movie (1966), by Michelangelo Antonioni, that questions the photography objectiveness analyzing the echo of the movie in Brazil from the photography image perspective. Our proposal is to think about photographers who took the movie as a reference to produce images linked to the artistic universe and photojournalism during the Brazilian Civil-Military Dictatorship. Starting from the idea that this artwork contributed to the reflection on the photographic image as statement of the real, we studied images produced by the photographers Armando Prado and Boris Kossoy, in order to observe photographies that moves from critical images in a subtle way to images that denounce the country’s political situation. Afterwards, from the collection of the photographers Armando Prado and Miguel Aun’s testimonies, we verify the repercussion of Blow-up in their trajectories, in an attempt to identify influences on the imaginary of artist-photographers in the construction of a critical and revolutionary visual culture as thought by Walter Benjamin (1994) in his essay the author as producer.